Hydrogeochemical variations related to seismic and volcanic activity in Kamchatka (Russia) - Biagi, P; Piccolo, R; Minafra, A; Castellana, L; Perna, G; Capozzi, V; Khatkevich, Y; Gordeev, E.; ERMINI, ANITA (Copernicus GmbH, 2004)
Starting from 1992, hydrogeochemical data have been collected with a mean sampling frequency of three days in the form of the pH value and of the most common ions and gases in the groundwater of a deep well located in the capital city Petropavlovsk of Kamchatka (Russia). On January 1, 1996 the Karymsky volcano, located 100 km far from the well in north-northeaster direction, started a strong eruption. Simultaneously a large (M = 6.9) earthquake occurred in the Karymsky area. On December 5, 1997 a very large (M = 7.7) earthquake occurred offshore, 350 km far from the well, in north- easter direction. The raw trends of the hydrogeochemical parameters at the well reveal clear variations occurred for both of the previous events. In the first case, the variations are defined by a clear premonitory phase; in the second one they are post seismic vari- ations and some permanent disturbance in the chemistry of the water appears. During the measurements time other large (M=7.0-7.3) earthquakes occurred at distances less than 250 km from the previous well in south and in east direction. On these occa- sions none evident variation appears in the previous trends. The phenomenology we pointed out reveals a strict structural connection between the Petropavlovsk area and the north-northeaster zone. At the same time it confirms that the appearance of precursors in hydrogeochemical parameters can be anisotropic in space. According to our opinion, this anisotropy could be valid also for other different parameters used in the research on earthquake precursors.